Career path of food science and technology professionals: Entry to the world of work. Issue 2 (April 2015) - Oreopoulou, Vassiliki; Giannou, Virginia; Lakner, Zoltan; Pittia, Paola; Mayor, Luis; Silva, Cristina L.M.; Costa, Rui
Abstract : The entrance in the job market of Food Science and Technology (FST) professionals was examined by a web-based survey conducted in Europe. The results highlight aspects that involve both the higher education and extracurricular qualifications and underline the different needs that education and training must fulfil. The field of higher education degree and gender affected the level of responsibility and the type of activity. FST professionals cover a wide range of tasks which require expertise that cannot be covered entirely by a single degree but these professionals show that are eager to expand their knowledge and skills. Highlights: The entrance in the job market of food professionals was surveyed in Europe. Qualifications, training and job characteristics were screened. Differences between countries are presented. Higher education degree and gender affected the level of responsibility. Higher education degree and gender affected the type of activity.